Exploring Customer Perceptions and Preferences: Study on Online Workshops for Tire Repair and Oil Change Services in DKI Jakarta - Elsa Herliyana; Nur Syifa Karimah; Sabrina Dwi Aprilia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This qualitative study aims to explore customer perceptions and preferences regarding online workshops for tire repair and oil change services in DKI Jakarta. Adopting a qualitative research model, the study utilizes purposive sampling to select participants from the target population. Data collection is conducted through in-depth interviews and thematic analysis of the collected data. The findings reveal insights into customers' attitudes, needs, and preferences towards online workshops for automotive maintenance. Through thematic analysis, common themes and patterns emerge, providing valuable insights for service providers and policymakers seeking to enhance the effectiveness and adoption of online workshops in the automotive service industry.